Motion picture and video lighting : for cinematographers, gaffers, and lighting technicians - Brown, Blain (New York, NY : Routledge, 2024)
"This fully revised and updated fourth edition of Motion Picture and Video Lighting explores the technical, aesthetic, and practical aspects of lighting for film and video. It covers not only how to light, but also why. Written by experienced author and filmmaker Blain Brown, this book emphasizes how the image, the mood, and the visual impact of a film are, to a great extent, determined by the skill and sensitivity of the director of photography in using lighting. It provides an indispensable, highly illustrated and comprehensive guide to making every scene look its best. Key topics include: Lighting sources, the lighting process, lighting basics, LED, tungsten, Kino-Flo, HMI, and plasma lights, methods of controlling light, planning your lighting, the basic methods: a lighting playbook, visual storytelling with light, understanding and controlling color, terminology, electricity and distribution, gripology, set operations, the team: DP, gaffer, grips, lighting technicians, technical issues, lighting for greenscreen/bluescreen, typical equipment orders for large and small jobs, lighting for high speed and macro photography, lighting plans for small, medium, and large films. This new edition has also been expanded to provide further guidance at the introductory level for students and those just starting in their careers. A robust accompanying companion website also includes up-to-date video tutorials and other resources for students and professionals alike"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Cinematography -- Lighting; Video recording -- Lighting